Digitization-based automation and occupational dynamics - Malin Gardberg; Fredrik Heyman; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2019)
We examine the relationship between occupational automation probabilities and employment dynamics over nearly two decades. We show that employment and wage shares of occupations with a higher automation risk have declined in Sweden over the period 1996-2013. This has occurred both in the aggregate private business sector but also within firms, where the wage share changes have been larger than the employment share changes. Combining the automation risk in workers' occupations with individual worker characteristics, we find substantial heterogeneity. This includes that education dampens the automation risk of workers, as the average automation probability of low-skilled workers is almost twice as high as of university graduates. Employment shares in high-risk occupations have moreover declined across all wage levels, and most so in high-wage occupations.
Keywords: J31; J62; O33; 330; Automation; Digitization; Employment shares; Wage shares